2022
DOI: 10.1002/adfm.202203520
|View full text |Cite
|
Sign up to set email alerts
|

Composition‐Dependent Morphology, Structure, and Catalytical Performance of Nickel–Iron Layered Double Hydroxide as Highly‐Efficient and Stable Anode Catalyst in Anion Exchange Membrane Water Electrolysis

Abstract: Water splitting is an environmentally friendly strategy to produce hydrogen but is limited by the oxygen evolution reaction (OER). Therefore, there is an urgent need to develop highly efficient electrocatalysts. Here, NiFe layered double hydroxides (NiFe LDH) with tunable Ni/Fe composition exhibit corresponding dependent morphology, layered structure, and chemical states, leading to higher activity and better stability than that of conventional NiFe LDH-based catalysts. The characterization data show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 94 publications
2
37
0
Order By: Relevance
“…8c, Jiang and co-workers effectively regulated the composition and morphology of NiFe LDH for OER. 58 The obtained single layer NiFe 3 LDH showed a low overpotential of 249 mV at 10 mA cm À2 and an ultrasmall Tafel slope of 24 mV dec À1 . In AEMWE, the Ni 3 Fe LDH achieved a high current density of 2 A cm À2 at 2.0 V, and maintained long-term stability for 400 h at 1 A cm À2 (Fig.…”
Section: Transition Metal Oxidesmentioning
confidence: 92%
See 2 more Smart Citations
“…8c, Jiang and co-workers effectively regulated the composition and morphology of NiFe LDH for OER. 58 The obtained single layer NiFe 3 LDH showed a low overpotential of 249 mV at 10 mA cm À2 and an ultrasmall Tafel slope of 24 mV dec À1 . In AEMWE, the Ni 3 Fe LDH achieved a high current density of 2 A cm À2 at 2.0 V, and maintained long-term stability for 400 h at 1 A cm À2 (Fig.…”
Section: Transition Metal Oxidesmentioning
confidence: 92%
“…The OER process in alkaline electrolytes involves the consumption of OH À in multiple steps. The widely recognized OER mechanisms can be summarized as the , 27 3, 28 4, 29 5, 30 6, 31 7, 32 8, 33 9, 34 10, 35 11, 36 12, 37 13, 38 14, 39 15, 40 16, 41 17, 42 18, 43 19, 44 20, 45 21, 46 22, 47 23, 48 24, 49 25, 50 26, 51 27, 52 28, 53 29, 54 30, 55 31, 56 32, 57 33, 58 34, 59 35, 60 36, 61 37, 62 38, 63 39, 64 40, 65 41. 66 (b): 1, 67 2, 32 3, 33 4, 35 5, 48 6, 68 7, 69 8, 70 9, 39 10, 62 11, 71 12, 41 13, 72 14, 53 15,…”
Section: Stability Issues Of Oer and Her Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the drafting of this publication, Jiang et al 194 reported Ni 3 Fe LDH synthesized by a co-precipitation method from Ni(NO 3 ) 2 and Fe(NO 3 ) 3 in alkaline solution, which exhibited a low overpotential of 249 mV at 10 mA cm −2 in 1 M KOH electrolyte, room temperature, with an ultra-small Tafel slope of 24 mV dec −1 . To evaluate stability, Ni 3 Fe LDH with a 0.2 mg cm −2 loading on Ni foam was tested at a fixed voltage of 1.6 V for 400 h in 1 M KOH.…”
Section: Catalysts Of the Oxygen Evolution Reaction (Oer) In Alkaline...mentioning
confidence: 99%
“…The NiFe LDH catalyst was synthesized by the precipitation method described in our previous work. [33] 3 mmol Ni(NO 3 ) 2 (nickel(II) nitrate hexahydrate) and 0.75 mmol Fe(NO 3 ) 3 (iron(II) nitrate hexahydrate) were added to an aqueous NaOH solution (0.15 mol/L) and stirred at 1000 rpm for 10 minutes at room temperature. Then the precipitate was washed with water and centrifuged, followed by ultrasonication for half an hour to achieve exfoliation.…”
Section: Chemicals and Materialsmentioning
confidence: 99%